MUSIK SEBAGAI MEDIA KRITIK SOSIAL : ANALISIS SEMIOTIKA LAGU BAYAR BAYAR BAYAR KARYA BAND SUKATANI - Poppi Damayanti; Ayu Resti Savitri (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2026)
The song titled "Bayar Bayar Bayar" is a work by the punk band Sukatani, which conveys a social critique from the songwriter to the listeners. It features straightforward, sharp, and critical lyrics regarding a widespread social issue: the practice of corruption by certain rogue police officers who violate regulations. This study aims to describe and analyze the effectiveness of music as a medium for social critique through the lens of Roland Barthes' semiotics.The research employs a descriptive qualitative method with a content analysis technique focused on the song's lyrics. The findings indicate that, denotatively, the lyrics depict the phenomenon of illegal levies (extortion) by unscrupulous officials, while connotatively, they represent public resistance against the hegemony of corrupt power.This research provides a scholarly contribution to the development of conflict communication studies within artistic works, where the effectiveness of music as a critical medium is measured not only by its lyrical content but also by the dialectics that emerge in the public sphere following the work's release. The findings suggest that although music possesses a strong emotional appeal to drive social change, its existence remains vulnerable to the limitations of freedom of expression in Indonesia. These results enrich the literature on the function of music as a channel for political aspiration while mapping the challenges faced by independent musicians regarding legal and institutional risks in the digital era. Keywords: Social Critique, Music, Roland Barthes, Semiotics.